A study on risk factors of coronary artery disease in Chong Qing city. (12th October 2011) - Ke-Chun, Wang; Xi, Wang; Dong-Ying, Zhang; Shu, Qin; Yu-Jing, Wang; Guang-Lei, Chang; Wen-Yi, He; Ying, Zhang
Abstract : Objective: To investigate the relationship between risk factors and coronary artery disease in Chong Qing city, and to provide scientific basis for preventing and intervening coronary artery disease. Methods: Four hundred and fifty eight inpatients who had been diagnosed with suspected coronary artery disease were divided into two groups: non-coronary artery disease group (NCAD) and coronary artery disease group (CAD), according to coronary angiography. The relationship between risk factors and coronary artery disease was then analysed. Results: (1) The rates of male, older age, smoking, hypertension and abnormal lipid metabolism were significantly higher in coronary artery disease group than those non-coronary artery disease group (p<0.05). (2) The rates of smoking, hypertension and diabetes mellitus were significantly higher in male coronary artery disease group than those non-coronary artery disease group (p<0.05). The rates of older, hypertension and abnormal lipid metabolism were significantly higher in female coronary artery disease group than those non-coronary artery disease group (p<0.05). (3) The rates of male, smoking, hypertension, diabetes mellitus and abnormal lipid metabolism were significantly higher in younger coronary artery disease group than those non-coronary artery disease group (p<0.05). The rate of hypertension and diabetes mellitus was significantly higher in older coronary artery disease group than those non-coronary artery disease group (p<0.05). (4) Multiple regression analyses indicated that age, gender, smoking, hypertension, diabetes mellitus and abnormal lipid metabolism were the most prominent risk factors. Conclusion: Age, gender, smoking, hypertension, diabetes mellitus and abnormal lipid metabolism are the most prominent risk factors of coronary artery disease in Chong Qing city.